Analytical Quality by Design Approach to Test Method Development and Validation in Drug Substance Manufacturing - N. V. V. S. S. Raman; Useni Reddy Mallu; Hanimi Reddy Bapatu (Journal of Chemistry)
Pharmaceutical industry has been emerging rapidly for the last decade by focusing on product Quality, Safety, and Efficacy. Pharmaceutical firms increased the number of product development by using scientific tools such as QbD (Quality by Design) and PAT (Process Analytical Technology). ICH guidelines Q8 to Q11 have discussed QbD implementation in API synthetic process and formulation development. ICH Q11 guidelines clearly discussed QbD approach for API synthesis with examples. Generic companies are implementing QbD approach in formulation development and even it is mandatory for USFDA perspective. As of now there is no specific requirements for AQbD (Analytical Quality by Design) and PAT in analytical development from all regulatory agencies. In this review, authors have discussed the implementation of QbD and AQbD simultaneously for API synthetic process and analytical methods development. AQbD key tools are identification of ATP (Analytical Target Profile), CQA (Critical Quality Attributes) with risk assessment, Method Optimization and Development with DoE, MODR (method operable design region), Control Strategy, AQbD Method Validation, and Continuous Method Monitoring (CMM). Simultaneous implementation of QbD activities in synthetic and analytical development will provide the highest quality product by minimizing the risks and even it is very good input for PAT approach.